Argumentação e formação do senso crítico: proposta de trabalho com o gênero anúncio - PASSINHO, Joelton da Silva (Universidade Federal do Pará, 2020)
In this study, the difficulties of argumentation presented by students of the 9th grade of Elementary School of a public school in the municipality of Curuçá-PA were investigated (through reading, oral and written activities), with the objective of elaborating a proposal of intervention that contributes to the accomplishment of more proficient readings and favors the development of the critical and reflexive sense of the students. The research, based on quantitative-qualitative sociolinguistics, involved the realization of several stages: (i) data collection from diagnostic activities; (ii) selection of the texts for the initial diagnosis; (iii) analysis of data and considerations about the most relevant items; (iv) preparation of the intervention activities (v) application of the proposed exercises and reflection on the results achieved; (vi) dissemination of students' final productions. The corpus consisted of data collected from the productions of 20 students (from the urban area and rural area, being 05 boys and 05 girls from each area), and the research was submitted to a methodology based on textual linguistics and with influence of the analysis based on authors such as Adam (2008), Abrel (2009), Bagno (2009), Ducrot (1987), Fiorin (2016) and Marcuschi (2008). The verification of the results made it possible to verify that students complete elementary school with low argumentative competence, since they demonstrate great difficulties to understand information that is not on the textual surface and, in most situations, do not question the ideas presented in the texts. Based on these findings, a didactic-methodological proposal was formulated with the purpose of intervening in the evidenced deficiencies, so that the student reaches greater argumentative competence in the later grades.